Design trends and future planning for inclusive development in tropical built environment - Abdul Rahim, Asiah; Abd Samad, Nur Amirah; W Seman, Wan Mohamad Amin (West Africa Built Environment Research (WABER) Conference, School of Construction Economics and Management, 2021)
A brief history of the introduction of Universal Design and Accessibility in Malaysia where it has been established since 1990 of three Malaysian Standards regarding design for access to buildings. Coping with the demands of providing accessibility for Persons with Disabilities (PwDs) and the elderly has been a challenge for these past three decades. The intention is to distinguish current Universal Design trends and the level of public and professional awareness of inclusive development. Furthermore, an exploration of integrating inclusive development within the tropical built environment and our social construct of Asian culture and lifestyle. As a summary, to cater design for diverse age and ability is esteemed in providing recommendations or innovation design solutions to accommodate access design that complements in creating an accessible built environment.